A scalable, dividing cell model for the robust propagation and quantification of human sporadic Creutzfeldt–Jakob disease prions - Akin Nihat; Parineeta Arora; Christian Schmidt; Melissa L. D. Rayner; Jacqueline Linehan; Sebastian Brandner; Simon Mead; John Collinge; Parmjit S. Jat (Proceedings of the National Academy of Sciences, 2026)
Prion diseases represent a unique biological paradigm with mechanistic parallels to other neurodegenerative conditions like Alzheimer’s and Parkinson’s diseases. However, the study of human prion pathobiology and the development of effective therapeutics has been severely constrained by the inability to propagate human prions in dividing cells—forcing reliance on costly and slow animal bioassays. Here, we report the generation of EKV cells—a humanized cell model which supports the robust, indefinite propagation of sporadic Creutzfeldt–Jakob disease (sCJD) prions. We demonstrate that these cells replicate bona fide human prion infectivity in culture—cell lysates induce lethal neurodegeneration in humanized mice that is clinically and neuropathologically indistinguishable from inoculation with sCJD-infected brain tissue. We use EKV cells to develop the Human Prion Assay (HPA), which quantifies sCJD infectivity with sensitivity comparable to gold-standard mouse bioassay, while reducing the experimental timeline from years to weeks. Furthermore, we demonstrate that established sCJD infection can be cured by an anti-prion protein antibody, validating the system as a high-throughput platform for drug discovery. This model bridges a critical translational gap, offering a renewable alternative to animal bioassays, a paradigm to dissect the biology of human sCJD prion disease and screen for therapeutic agents.